Teprotumumab: The Dawn of Therapies in Moderate-to-Severe Thyroid-Associated Ophthalmopathy - Ding, Yizhi; Yang, Shaoqin; Gao, Hua (Hormone and Metabolic Research, 2021)
Thyroid-associated ophthalmopathy (TAO) is a potentially sight-threatening ocular disease. About 3–5% of patients with TAO have severe disease with intense pain, inflammation, and sight-threatening corneal ulceration or compressive optic neuropathy. The current treatments of TAO are often suboptimal, mainly because the existing therapies do not target the pathogenesis of the disease. TAO mechanism is unclear. Ocular fibrocytes express relatively high levels of the functional TSH receptor (TSHR), and many indirect evidences support its participation. Over expression of insulin-like growth factor-1 receptor (IGF-IR) in fibroblasts, leading to inappropriate expression of inflammatory factors, production of hyaluronic acid and cell activation in orbital fibroblasts are also possible mechanisms. IGF-1R and TSHR form a physical and functional signaling complex. Inhibition of IGF-IR activity leads to the attenuation of signaling initiated at either receptor. Teprotumumab (TMB) is a human immunoglobulin G1 monoclonal antibody, binding to IGF-IR. Recently two TMB clinical trials had been implemented in TAO patients, indicating dramatic reductions in disease activity and severity, which approved its use for the treatment of TAO in the US. This review summarizes the treatments of TAO, focusing on the pathogenesis of IGF-1R in TAO and its application prospects.
Keywords: thyroid eye disease; proptosis; treatment; insulin-like growth factor I receptor; monoclonal antibody; teprotumumab